Enhance the Electrical Performance of TiO2 NTAs Decorated with Cobalt and Compatible with Environmentally Friendly Electrolytes - Hasan, Bassam Baqer; Salman, Taghried Ali; Ayal, Asmaa Kadim (Iraqi Journal of Science, 2025)
Titanium dioxide nanotube arrays (TiO2 NTAs) were successfully decorated with nanoclusters of cobalt by an electrochemical deposition method. This Co-TiO2 NTAs nanostructure exhibited high compatibility with aluminum chloride\ chloroacetamide (an ionic liquid) and calcium chloride dihydrate\ acetamide (a deep eutectic solvent), leading to significant improvements in the electrochemical properties of the system. Significantly, this led to a discernible augmentation in both potential and current values, concomitant with a decrease in internal resistance. The presence of cobalt facilitated a faster transfer of electric charge, enhancing the overall efficiency of the system. Moreover, the incorporation of cobalt exhibited a beneficial effect on the preservation of ideal operational temperatures in the electric cells. The temperature remained below the permissible limit during both the charging and discharging processes. The utilization of scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) provided comprehensive visualization of the Co-TiO2 NTAs surface.